Prodromal depression in pancreatic cancer: Retrospective evaluation on ten patients. Issue 3 (24th June 2014) - Sebti, Johan; Desseigne, Françoise; Saltel, Pierre
Abstract: Objective: Since the description by Yaskin in 1931, it has been observed that pancreatic cancer and depression are two clinical entities that share a high affinity. This observation relies on the higher incidence of depressive syndromes associated with pancreatic cancer than in any other type of digestive tumor, and on the possible occurrence of depressive symptoms several months before the diagnosis of cancer. We present here a series of cases whose screening returned positive for depression-related diagnoses in the months prior to revelation of the cancer. Method: We employed a structured psychiatric interview based on DSM–IV criteria (SCID–I). The diagnoses considered were major depressive episode, minor depressive episode, and subsyndromal depression. All subjects were free of psychiatric history. Results: Some 15 patients were initially included: 10 presented compatible criteria for a past depressive episode, 2 presented a major depressive episode, 4 met the diagnosis of minor depression, and 4 evidenced subsyndromal depression over the one-year period prior to cancer diagnosis. Significance of results: This series of cases is consistent with previous work on the subject that suggested an increased vulnerability to depressive events in the premorbid phase of pancreatic cancer. If the possibility of depressive syndromes constituting the early stages of neoplastic disease is a common idea, it is still impossible to determine the natural history of these two disorders and therefore their causal linkage.